(untitled) (Bangladesh Journal of Child Health, 2024)
Introduction: Disorder of sex development (DSD) is defined as a condition where the development of gonadal, chromosomal or anatomic sex is atypical. Objective: To study the clinical and laboratory profile of patients with disorders of sex development (DSD) and classify them. Methods: A retrospective study was conducted in BSMMU from 1st May 2016 to 31st December 2021 including all patients diagnosed with DSD. Data were obtained by reviewing the medical records of the patients. Results: A total 67 patients were diagnosed as DSD. Among them 30 patients (44.8%) had 46,XX DSD, 22 patients (32.8%) had 46,XY DSD, 13 patients (19.4%) had sex chromosome DSD and 2 patients (2.9%) had ovotesticular DSD. Majority (60%) of the patients with 46,XX DSD were diagnosed as congenital adrenal hyperplasia (CAH) followed by adrenal tumor (16.7%) and patients with partial trisomy of chromosome 9q (16.7%). Among 22 patients with 46,XY DSD, eight patients (36.3%) had androgen biosynthetic defect, 6 cases (27.2%) were under virilized CAH and 2 patients (9%) had androgen insensitivity syndrome. Majority of sex chromosome DSD were turner syndrome (69.2%). Only 2 patient had mixed gonadal dysgenesis. Thirteen percent of the children with 46, XX DSD were reared as male and 27% of the 46, XY DSD cases were reared as female. Conclusion: Congenital adrenal hyperplasia is the most common cause of DSD. Majority of 46 XY, DSD is due to androgen bio synthetic defect while CAH is the most common cause of 46XX, DSD. Rare chromosomal disorders are also found among DSD cases. Bangladesh J Child Health 2023; Vol 47 (2) : 103-108